2022
DOI: 10.1002/hed.27064
|View full text |Cite
|
Sign up to set email alerts
|

Medicare reimbursement trends from 2000 to 2020 in head and neck surgical oncology

Abstract: Background Considering limited data exploring reimbursement trends at the subspecialty level within head and neck surgical oncology, we sought to characterize these trends for head and neck‐specific codes from 2000 to 2020. Methods Using the Centers for Medicare and Medicaid Services' Physician Fee Schedule Look‐Up Tool, reimbursement data, adjusted to 2020 U.S. dollars, for 37 head and neck surgical oncologic procedure codes were collected from 2000 to 2020. Results From 2000 to 2020, despite gross reimbursem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…This study found a 20.3% inflation‐adjusted decline in reimbursement of laryngeal procedures. Though our study looked at a greater number of procedures within laryngology, this result is largely in line with the recent findings of Quereshy et al who found an inflation‐adjusted decline of 19.4% among head and neck surgical oncology CPT codes 12 and Schartz et al who found an inflation‐adjusted decline of 21.2% among otology procedures 10 . This inflation‐adjusted decline is in sharp contrast to the 37.6% and 43.1% inflation‐adjusted decline seen in commonly performed otolaryngology procedures 9 and rhinology procedures, 11 respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study found a 20.3% inflation‐adjusted decline in reimbursement of laryngeal procedures. Though our study looked at a greater number of procedures within laryngology, this result is largely in line with the recent findings of Quereshy et al who found an inflation‐adjusted decline of 19.4% among head and neck surgical oncology CPT codes 12 and Schartz et al who found an inflation‐adjusted decline of 21.2% among otology procedures 10 . This inflation‐adjusted decline is in sharp contrast to the 37.6% and 43.1% inflation‐adjusted decline seen in commonly performed otolaryngology procedures 9 and rhinology procedures, 11 respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In approximately the last 2 decades, after adjusting for inflation, reimbursements have declined 25.8% in neurosurgery, 4 24.4% in general surgery, 5 29.0% in orthopedic surgery, 6 14.0% in reconstructive plastic surgery, 7 and 29.1% in emergency medicine 8 . Similar, yet further declining, trends have been seen in the field of otolaryngology with inflation‐adjusted reimbursements falling 37.6% for the 20 most performed otolaryngology procedures, 9 21.2% for otology procedures, 10 43.1% for rhinology procedures, 11 and 19.4% for head and neck surgical oncology procedures 12 . The objective of this study is to investigate Medicare reimbursement trends for commonly performed laryngeal procedures.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have examined reimbursement trends in surgical and radiation oncology and found notable decreases in most of the procedure codes evaluated 7–9 . However, to the author's best knowledge, no study to date has evaluated the reimbursement of physicians through the PFS for procedures in hematology/oncology.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Previous studies have examined reimbursement trends in surgical and radiation oncology and found notable decreases in most of the procedure codes evaluated. [7][8][9] However, to the author's best knowledge, no study to date has evaluated the reimbursement of physicians through the PFS for procedures in hematology/oncology. The aim of this study was to evaluate the trends in reimbursement for hematology/oncology procedures between 2012 to 2023 as decreases in reimbursement rates could have implications for the accessibility of hematology/oncology services and sustainability of these practices.…”
Section: Introductionmentioning
confidence: 99%